SISTEM AKUNTANSI PERSEDIAAN BAHAN BAKU PADA PT INDUSTRI KAPAL INDONESIA (PERSERO) - Ahmad Firdaus; Siswati Rachman (Pusat Riset dan Inovasi Nasional, 2022)
The research aims to determine the application of the Raw Material inventory Accounting System at PT Industri Kapal ndonesia (Persero). The type of research used s descriptive qualitative. Data obtained through observation, interviews, and documentation. The research conducted from July to September 2021. The results showed that the accounting system for raw material inventory at PT Industri Kapal Indonesia (Persero) has been effective, this can be seen by the existence of interrelated functions. Then the inventory recording method used is the perpetual recording method and the FIFO (First In First Out) valuation method. And the procedures that form the inventory system at PT Industri Kapal Indonesia (Persero) are quite good because of the division of tasks and documents that can be accounted for.